The use of PCR/Electrospray Ionization-Time-of-Flight-Mass Spectrometry (PCR/ESI-TOF-MS) to detect bacterial and fungal colonization in healthy military service members. Issue 1 (December 2016) - Vetor, Ryan; Murray, Clinton; Mende, Katrin; Melton-Kreft, Rachel; Akers, Kevin; Wenke, Joseph; Spirk, Tracy; Guymon, Charles; Zera, Wendy; Beckius, Miriam; Schnaubelt, Elizabeth; Ehrlich, Garth; et al.
Abstract Background The role of microbial colonization in disease is complex. Novel molecular tools to detect colonization offer theoretical improvements over traditional methods. We evaluated PCR/Electrospray Ionization-Time-of-Flight-Mass Spectrometry (PCR/ESI-TOF-MS) as a screening tool to study colonization of healthy military service members. Methods We assessed 101 healthy Soldiers using PCR/ESI-TOF-MS on nares, oropharynx, and groin specimens for the presence of gram-positive and gram-negative bacteria (GNB), fungi, and antibiotic resistance genes. A second set of swabs was processed by traditional culture, followed by identification using the BD Phoenix automated system; comparison between PCR/ESI-TOF-MS and culture was carried out only for GNB. Results Using PCR/ESI-TOF-MS, at least one colonizing organism was found on each individual: mean (SD) number of organisms per subject of 11.8(2.8). The mean number of organisms in the nares, groin and oropharynx was 3.8(1.3), 3.8(1.4) and 4.2(2), respectively. The most commonly detected organisms were aerobic gram-positive bacteria: primarily coagulase-negativeStaphylococcus (101 subjects: 341 organisms), Streptococcus pneumoniae (54 subjects: 57 organisms), Staphylococcus aureus (58 subjects: 80 organisms) andNocardia asteroides (45 subjects: 50 organisms). ThemecA gene was found in 96 subjects. The most commonly found GNB wasHaemophilus influenzae (20 subjects: 21 organisms) and the most common anaerobe wasPropionibacterium acnes (59 subjects).Saccharomyces species (30 subjects) were the most common fungi detected. Only one GNB (naresE. coli ) was identified in the same subject by both diagnostic systems. Conclusion PCR/ESI-TOF-MS detected common colonizing organisms and identified more typically-virulent bacteria in asymptomatic, healthy adults. PCR/ESI-TOF-MS appears to be a useful method for detecting bacterial and fungal organisms, but further clinical correlation and validation studies are needed.